Correction: The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Exosomal miR-21-5p from ectopic endometrial stromal cells drives fibrosis progression in endometriosis through direct VHL targeting - Jia-Hao Chen; Yi-Hong Lei; Dian-Chao Lin; Hua-Ying Zhang; Zhi-Xiong Huang; Ruo-Fan Huang; Pei-Tong Wei; Meng-Jie Yang; Xin-Yu Ding; Wei-Dong Zhou; Qiong-Hua Chen (Human Cell, 2026)

CCL21/CCR7 axis regulates VEGF-D m6A modification to drive lymphangiogenesis and lymphatic metastasis in gallbladder cancer - Zhenheng Wu; Xinran Cai; Lei Jiang; Bin Lin; Wei Pan; Shengzhe Lin; Yanling Chen; Haijie Hong (Human Cell, 2026)
Gallbladder cancer (GBC), the most common malignancy of the biliary tract, exhibits a high propensity for lymphatic system invasion. However, the mechanisms underlying lymphatic metastasis in GBC remain poorly understood. Here, we demonstrate that C–C motif chemokine ligand 21 (CCL21) is significantly upregulated in GBC and positively correlates with lymphatic vessel density and lymph node metastasis. Both in vivo and in vitro experiments confirm that CCL21/CCR7 axis promotes lymphangiogenesis and lymphatic metastasis in GBC. Mechanistically, CCL21/CCR7 modulates Vascular Endothelial Growth Factor-D (VEGF-D) mRNA N6-Methyladenosine (m 6 A) modification in an AlkB homolog 5 (ALKBH5)-dependent manner, thereby regulating VEGF-D protein expression. Site-directed mutagenesis experiments reveal that m 6 A modification sites in the coding sequence (CDS) region of VEGF-D mRNA are critical for VEGF-D protein regulation. Collectively, our findings highlight that CCL21/CCR7 regulates VEGF-D expression via m 6 A modification, driving lymphatic metastasis in GBC.

Targeting eIF5A2 hypusination with bikinin sensitizes hepatocellular carcinoma to lenvatinib by suppressing TFEB-mediated autophagy - Shuqian Wang; Qingyun Zhou; Qiaomei Lin; Shufen Zhang; Ying Cai; Fangnan Wu; Fangyuan Kuang; Lianghui Wang; Shangzhi Xie; Jiahua Lan; Li Zheng; Guodong Xu; et al. (Human Cell, 2026)

Matriptase proteolysis selectively drives disassembly and internalization of the claudin-7 complex while preserving E-cadherin - Yu-Ling A. Kao; He-Yu Huang; Yin S. Yu; Nanxi Huang; Ya-Chin Chan; Chen-Ray Lee; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2026)

Bone marrow mesenchymal stem cell-derived exosomes exert therapeutic effects on inflammatory bowel disease through miR-148a-3p/Ets-1-dependent inhibition of pyroptosis - Feilong Zhang; Ji Song; Yunjiao Zhang; Hejun Hu; Ping Zhou; Caixiao Xu; Meinan Zhan; Anna Hou; Xiangli Lin; Wenjuan Shen (Human Cell, 2026)

The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Bisphosphoglycerate mutase is involved in glucose metabolism and progression of nonalcoholic fatty liver disease based on liver organoids - Zheng Zhou; Xiyan Zheng; Xianqing Chen; Maoyun Xie; Fei Du; Zhiqun Lin; Xianjie Shi (Human Cell, 2026)

CBC3T-3: a novel patient-derived cisplatin-resistant distal cholangiocarcinoma cell line harboring multiple TP53 missense mutations - Jiahui Xi; Mingzhen Bai; Ruyang Zhong; Chongfei Huang; Ruoshui An; Long Gao; Haidong Ma; Liang Tian; Jinyu Zhao; Ningzu Jiang; Xiang He; Leiqing Wang; et al. (Human Cell, 2026)
Distal cholangiocarcinoma (dCCA) is a malignant tumor characterized by a challenging diagnosis, high invasiveness, and extremely poor prognosis. Research on dCCA is limited by the scarcity of reliable patient-derived preclinical tumor models. This study established a novel human distal cholangiocarcinoma cell line, CBC3T-3, and systematically characterized its biological properties, genomic features, and potential for clinical application. This cell line was extracted from postoperative distal cholangiocarcinoma tumor from a 54-year-old male patient. It was stably passaged (> 50 generations) through primary culture and condition optimization, preserving the same pathology as that of the primary tumor. Whole-exome sequencing (WES) confirmed somatic mutations, tumor mutation burden, single-sample clonal structure, driver genes, and drug resistance genes in CBC3T-3 cells, revealing their genomic characteristics. Functional assays demonstrated that CBC3T-3 cells exhibit strong capabilities for proliferation, migration, and invasion in vitro. In a subcutaneous xenograft model in immunodeficient mice, palpable tumor nodules developed within 4 weeks, reflecting the clinical characteristics of rapidly progressive disease. Drug sensitivity analysis revealed that, compared with TFK-1 cells, CBC3T-3 cells presented significantly greater responses to paclitaxel, gemcitabine, and oxaliplatin but relatively poor responses to 5-FU and cisplatin. The integration of drug resistance gene findings from WES suggests that TP53 missense mutations may mediate primary resistance to cisplatin. The establishment of the CBC3T-3 cell line enhances the research toolkit for dCCA. Its genomic characteristics and functional plasticity provide a reliable preclinical tumor model for developing precision therapies and investigating drug resistance mechanisms.

OTUB2 aggravates pathological cardiac hypertrophy through Rac1 activation - Junhui Xing; Lijin Lin; Yi Zhao; Zhen Shen; Yuzhen Wei; Xiaofei Xue; Fen Qin; Hengdao Liu (Human Cell, 2025)

TPM3–NTRK1 fusion confers resistance to osimertinib in lung adenocarcinoma: a model in a continuous cell line - Fang Cao; Jiayin Dai; Kun Dong; Zhenli Yang; Yanli Zhu; Changsong Qi; Dongmei Lin; Xiaocui Bian; Yuqin Liu (Human Cell, 2025)

Cedrol impedes lung cancer metastasis by reducing tumor-associated macrophage polarization mediated by MYC-driven aerobic glycolysis - Qingsheng Li; Yuxi Liu; Lin Zhang; Yi Zheng; Xiaofan Feng; Yanjie Wang (Human Cell, 2025)

Correction: IL-32/NFκB/miR-205 loop sustains the high expression of IL-32 and enhances the motility of cervical cancer cells - Jianbing Liu; Kai Yang; Xiaoyu Lin; Jing Xu; Xiaohua Cui; Jianqing Hao; Wei Wang; Wenhao Wang; Li Li; Min Hao (Human Cell, 2025)

KDELR3 is transcriptionally activated by FOXM1 and accelerates lung adenocarcinoma growth and metastasis via inhibiting endoplasmic reticulum stress-induced cell apoptosis - Cheng Wang; Zhaoxuan Wang; Shiqing Wang; Lin Jing; Chundong Gu (Human Cell, 2025)

Taxifolin regulates SLC31A1-mediated cuproptosis and tumor progression in hepatocellular carcinoma - Jike Li; Yuelian Wang; Lei Bao; Guo Chen; Qing Ye; Chengshi He; Lin Liu; Mei Luo (Human Cell, 2025)

Long non-coding RNA MSC-AS1 confers imatinib resistance of gastrointestinal stromal tumor cells by activating FNDC1 and ANLN-mediated PI3K/AKT pathway - Lin Chen; Yongjian Gao; Huaixi Yang; Yanzhuo Su; Yunxin Zhang; Lin Lou; Xuefeng Wang; Dayong Ding (Human Cell, 2025)

Pancreatic cancer-derived exosomal miR-510 promotes macrophage M2 polarization and facilitates cancer cell aggressive phenotypes - Tao Wang; Lin Ye; Yingjie Zhou; Xionghan Zhang; Renjian Li; Yi Zhou; Jun Weng; Qingrong Mo; Yaqun Yu (Human Cell, 2024)

Development of 3D-iNET ORION: a novel, pre-clinical, three-dimensional in vitro cell model for modeling human metastatic neuroendocrine tumor of the pancreas - Jan Strnadel; Mark A. Valasek; Grace Y. Lin; Huahui Lin; Ann M. Ponsford Tipps; Sang Myung Woo; Ken Fujimura; Huawei Wang; Sunkyu Choi; Jack Bui; Christopher Hermosillo; Kristen Jepsen; et al. (Human Cell, 2024)
Neuroendocrine tumors (NETs) of the pancreas are rare neoplasms that present complex challenges to diagnosis and treatment due to their indolent course. The incidence of pancreatic neuroendocrine tumors has increased significantly over the past two decades. A limited number of pancreatic neuroendocrine cell lines are currently available for the research. Here, we present 3D-iNET ORION, a novel 3-dimensional (spheroid) cell line, isolated from human pancreatic neuroendocrine tumor liver metastasis. Three-dimensionally grown (3D) cancer cell lines have gained interest over the past years as 3D cancer cell lines better recapitulate the in vivo structure of tumors, and are more suitable for in vitro and in vivo experiments. 3D-iNET ORION cancer cell line showed high potential to form tumorspheres when embedded in Matrigel matrix and expresses synaptophysin and EpCAM. Electron microscopy analysis of cancer cell line proved the presence of dense neurosecretory granules. When xenografted into athymic mice, 3D-iNET ORION cells produce slow-growing tumors, positive for chromogranin and synaptophysin. Human Core Exome Panel Analysis has shown that 3DiNET ORION cell line retains the genetic aberration profile detected in the original tumor. In conclusion, our newly developed neuroendocrine cancer cell line can be considered as a new research tool for in vitro and in vivo experiments.

KIN17 functions in DNA damage repair and chemosensitivity by modulating RAD51 in hepatocellular carcinoma - Xueran Huang; Zichang Dai; Biyun Zeng; Xiangyan Xiao; Kashif Rafiq Zahid; Xiaocong Lin; Tiancai Liu; Tao Zeng (Human Cell, 2024)

IL-32/NFκB/miR-205 loop sustains the high expression of IL-32 and enhances the motility of cervical cancer cells - Jianbing Liu; Kai Yang; Xiaoyu Lin; Jing Xu; Xiaohua Cui; Jianqing Hao; Wei Wang; Wenhao Wang; Li Li; Min Hao (Human Cell, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Pathological mechanisms of cold and mechanical stress in modulating cancer progression - Yun-jing Hou; Xin-xin Yang; Lin He; Hong-xue Meng (Human Cell, 2024)

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

PIAS1 impedes vascular endothelial injury and atherosclerotic plaque formation in diabetes by blocking the RUNX3/TSP-1 axis - Qingsong Jin; Tiantian Zhao; Liangyan Lin; Xiaoyan Yao; Yaqin Teng; Dongdong Zhang; Yongjun Jin; Meizi Yang (Human Cell, 2023)

Long noncoding RNA XLOC_006786 inhibits the proliferation, invasion and metastasis of osteosarcoma cells through NOTCH3 signaling pathway by targeting miR-491-5p - Jia-Yi Xu; Yang-fan Lv; Ya Cao; Hong-min Ma; Xiang-lin Hao; Lu Huang; Xue-feng Tang; Qiao-nan Guo (Human Cell, 2023)

Cofilin-1 induces acute kidney injury via the promotion of endoplasmic reticulum stress-mediated ferroptosis - Sihao Lin; Jie Wang; Bin Cao; Yang Huang; Xujun Sheng; Yingjian Zhu (Human Cell, 2023)
Ischemia–reperfusion injury (IRI) leads to acute kidney injury (AKI), which poses serious threat to public health and society. Many clinical studies were conducted to evaluate several biomarkers in AKI, among which Cofilin-1 remains to be a very promising one. To explore the potential mechanism of Cofilin-1 in AKI, we established an oxygen-glucose-deprivation (OGD)-induced AKI cell model. The overexpression and knock-down Cofilin-1 were used for gain- and loss-of-function. Pharmacological inhibitors were employed to study the related pathways. The results showed that Cofilin-1 was significantly upregulated in AKI cells, knocking down Cofilin-1 protected cells against the effect of OGD treatment and alleviated AKI phenotypes. Overexpression of Cofilin-1 might induce AKI by triggering ferroptosis, inhibiting NF-κB signaling or ER stress pathway attenuated Cofilin-1 induced lipid peroxidation and AKI. We also validated our findings in IRI-induced AKI mouse models in vivo. Our work elucidated that Cofilin-1 might induce AKI via promoting ER stress-mediated ferroptosis and argues it as a biomarker for early diagnosis of AKI. We also expect to offer novel insights on future therapeutic interventions.

Downregulation of the long noncoding RNA DSCR9 (Down syndrome critical region 9) delays breast cancer progression by modulating microRNA-504-5p-dependent G protein-coupled receptor 65 - Mingzhu Li; Conglin Lin; Zhibing Cai (Human Cell, 2023)

Correction: PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2023)

HAI-1 is required for the novel role of FGFBP1 in maintenance of cell morphology and F-actin rearrangement in human keratinocytes - Dajun D. Lu; Nanxi Huang; Sheng-Wen A. Li; Jessica R. Fang; Chih-Hsin Lai; Jehng-Kang Wang; Khee-Siang Chan; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2023)

Prognostic and functional roles of EIF4G1 in lung squamous cell carcinoma - Baoxin Bai; Lin Dong; Minghao Feng; Zhiwen Zhang; Ying Lu; Zengguang Xu; Yali Liu (Human Cell, 2023)
Eukaryotic translation initiation factor 4 gamma 1 (EIF4G1) is highly expressed in many cancers and affects their occurrence and development. However, the effect of EIF4G1 on the prognosis, biological function and the relevant mechanism in lung squamous cell carcinoma (LSCC) is unclear. Through clinical cases, Cox’s proportional hazard model and Kaplan–Meier plotter survival analysis, we find the expression levels of EIF4G1 are dependent on age and clinical stage, high expression of EIF4G1 could be used to predict the overall survival of LSCC patients. LSCC cell line NCI-H1703, NCI-H226 and SK-MES-1infected with EIF4G1 siRNA are used to detect the function of EIF4G1 with cell proliferation and tumorigenesis in vivo and vitro. The data show that EIF4G1 promotes tumor cell proliferation and the G1/S transition of cell cycle in LSCC, then the biological function of LSCC is effected by the AKT/mTOR pathway. Above all, these results have demonstrated that EIF4G1 promotes LSCC cell proliferation and may represent an indicator of prognosis in LSCC.

A prognostic cuproptosis-related lncRNA predictive signature for bladder cancer patients - Shaoqin Jiang; Jili Zhang; Qi Fan; Zhihao Li; Ruiling Dou; Zequn Lin; Zhenlin Chen; Yue Xu; Zhangcheng Huang; Jingyuan Lan; Wenwen Lin; Sijie Xu; et al. (Human Cell, 2023)

PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2022)
Acute kidney injury (AKI) is a common severe acute syndrome caused by multiple factors and is characterized by a rapid decline in renal function during a short period. Bone marrow mesenchymal stromal cells (BMSCs) are effective in treating AKI. However, the mechanism of their beneficial effects remains unclear. PTEN-induced kinase 1 (PINK1) may play an important role in kidney tissue repair. In this study, we explored the effect of PINK1 overexpression on enhancing BMSC-mediated repair of AKI. In this study, ischaemia/reperfusion-induced AKI (IRI-AKI) in mice and a hypoxia-reoxygenation model in cells were established, and the indices were examined by pathology and immunology experiments. After ischaemia/reperfusion, PINK1 overexpression reduced apoptosis in injured kidney tissue cell, decreased T lymphocyte infiltration, increased macrophage infiltration, and alleviated the inflammatory response. PINK1 relieved the stress response of BMSCs and renal tubular epithelial cells (RTECs), reduced apoptosis, altered the release of inflammatory factors, and reduced the proliferation of peripheral blood mononuclear cells (PBMCs). In conclusion, BMSCs and RTECs undergo stress responses in response to hypoxia, inflammation and other conditions, and overexpressing PINK1 in BMSCs could enhance their ability to resist these stress reactions. Furthermore, PINK1 overexpression can regulate the distribution of immune cells and improve the inflammatory response. The regulation of mitochondrial autophagy during IRI-AKI maintains mitochondrial homeostasis and protects renal function. The results of this study provide new strategies and experimental evidence for BMSC-mediated repair of IRI-AKI.

MiR-100-5p inhibits osteogenic differentiation of human bone mesenchymal stromal cells by targeting TMEM135 - Rui Wang; Miao Zhang; Ying Hu; Juan He; Qiao Lin; Nianchun Peng (Human Cell, 2022)

SESN1, negatively regulated by miR-377-3p, suppresses invasive growth of head and neck squamous cell carcinoma by interaction with SMAD3 - Chi Zhang; Lin Ren; Hongjian Zhang; Shiwen Yang; Miao Deng; Lihong He; Ruoyan Cao; Chuanjiang Zhao; Juan Xia (Human Cell, 2022)

Construction and comprehensive analysis of a lncRNA–mRNA interactive network to reveal a potential lncRNA for hepatic encephalopathy development - Chihao Zhang; Wei Ni; Yiming Zhu; Jiayun Lin; Hongjie Li; Zhifeng Zhao; Ke Wang; Haizhong Huo; Meng Luo (Human Cell, 2022)

Knockout of GGPPS1 restrains rab37-mediated autophagy in response to ventilator-induced lung injury - Zexu Wang; Meizi Chen; Xia Pan; Li Wang; Cheng Yin; Qiuqi Lin; Jingjing Jiang; Yunlei Zhang; Bing Wan (Human Cell, 2022)

The difference in the intracellular Arg/Lys-rich and EHLVY motifs contributes to distinct subcellular distribution of HAI-1 versus HAI-2 - Nanxi Huang; Robert B. Barndt; Dajun D. Lu; Qiaochu Wang; Shih-Ming Huang; Jehng-Kang Wang; Ping-Ying Chang; Chao-Yang Chen; Je-Ming Hu; Hui-Chen Su; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2022)

Overexpression of long noncoding RNA MCM3AP-AS1 promotes osteogenic differentiation of dental pulp stem cells via miR-143-3p/IGFBP5 axis - Changwei Yang; Xuehong Xu; Pingting Lin; Bizhu Luo; Shufang Luo; Honglan Huang; Jianyu Zhu; Meie Huang; Shuhai Peng; Qianju Wu; Lu Yin (Human Cell, 2022)

Histone deacetylase 6-mediated downregulation of TMEM100 expedites the development and progression of non-small cell lung cancer - Yanyun Wang; Minwen Ha; Man Li; Lin Zhang; Yitong Chen (Human Cell, 2022)

Mesenchymal stem cell-derived exosomes block malignant behaviors of hepatocellular carcinoma stem cells through a lncRNA C5orf66-AS1/microRNA-127-3p/DUSP1/ERK axis - Hao Gu; Chao Yan; Haijun Wan; Lin Wu; Junjie Liu; Zhiqiang Zhu; Dazhi Gao (Human Cell, 2021)

Profiling heterogenous sizes of circulating tumor microemboli to track therapeutic resistance and prognosis in advanced gastric cancer - Yang Chen; Jiajia Yuan; Yanyan Li; Xue Li; Ying Yang; Jian Li; Yilin Li; Lin Shen (Human Cell, 2021)
Circulating tumor microemboli (CTM) aggregated by ≥ 2 circulating tumor cells (CTCs) are more migratory than single CTCs. Aside from the plasticity in their molecular characteristics, which have been considered tumor migration, CTM also possesses high size heterogeneity. This study, therefore, systematically investigated the heterogeneous sizes of CTM and their involvement in therapeutic resistance in 114 patients with advanced gastric cancer (GC) using a pre-established surface molecule-independent subtraction enrichment (SE)-iFISH strategy. CTM, which was pre-therapeutically detected in 33.3% of GC patients, can further form in another 34.78% of patients following chemo-/targeted therapies. The presence of CTM is relevant to liver metastasis as well as higher CTC levels (≥ 5/6 mL). Further size-based profiling of GC-CTM revealed that CTM with 2 CTCs (CTM 2 ) was the dominant subtype, accounting for 50.0% of all detected GC-CTMs. However, CTM with 3–4 CTCs (CTM 3–4 ) specifically associates with chemo-/targeted therapeutic resistance and inferior prognosis. Patients with ≥ 1 CTM 3–4 /6 mL have shorter median progression-free survival and median overall survival. Unlike CTM 2 and CTM 3–4 , which are detectable in pre-therapy and post-therapy, larger aggregated CTM ≥5 (CTM with ≥ 5 CTCs) was only intra-therapeutically detected in four HER2 + GC patients, of which three experienced liver metastases. Obtained results suggested that the cluster size of GC-CTM should be dynamically profiled beyond pre-therapeutic whole CTM enumeration in terms of chemo-/targeted resistance or metastasis monitoring. GC-CTM 3–4 could be a potential indicator of therapeutic resistance, while the dynamic presence of GC-CTM ≥5 implies liver metastasis in HER2 + GC patients.

Long non-coding RNA FGD5-AS1 enhances osteosarcoma cell proliferation and migration by targeting miR-506-3p/RAB3D axis - Congda Li; Xiangbo Lin; Caiyun Zhang; Lei Wan; Jijun Yin; Bin Wang (Human Cell, 2021)

S100A14 inhibits cell growth and epithelial–mesenchymal transition (EMT) in prostate cancer through FAT1-mediated Hippo signaling pathway - Shaoqin Jiang; Yaru Zhu; Zhenlin Chen; Zhangcheng Huang; Bingqiao Liu; Yue Xu; Zhihao Li; Zequn Lin; Mengqiang Li (Human Cell, 2021)

LINC00200 contributes to the chemoresistance to oxaliplatin of gastric cancer cells via regulating E2F1/RAD51 axis - Mengxin Lin; Meifang Xu; Zongbin Xu; Zongqi Weng; Bingqiang Lin; Yanqin Lan; Qing Liu; Xiaoyan Lin; Jie Pan (Human Cell, 2021)

Stress-induced phosphoprotein 1 facilitates breast cancer cell progression and indicates poor prognosis for breast cancer patients - Lizhi Lin; Jialiang Wen; Bangyi Lin; Erjie Xia; Chen Zheng; Lechi Ye; Yinghao Wang; Ouchen Wang; Yizuo Chen (Human Cell, 2021)

Targeted deletion of HAI-1 increases prostasin proteolysis but decreases matriptase proteolysis in human keratinocytes - Dajun D. Lu; Yayun Gu; Sheng-Wen A. Li; Robert J. Barndt; Shih-Ming Huang; Jehng-Kang Wang; Hui Chen Su; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2021)

RING-finger protein 5 promotes hepatocellular carcinoma progression and predicts poor prognosis - Yi Zhang; Jie Li; Huayang Chen; Changmao Zhang; Song You; Yue Zhao; Xiaoning Lin; Yaqi Yu; Fei Fang; Ting Fang; Xiaomin Wang (Human Cell, 2021)

MiR-27b-3p inhibits the progression of renal fibrosis via suppressing STAT1 - Lin Bai; Yongtao Lin; Juan Xie; Yiyuan Zhang; Hongwu Wang; Donghui Zheng (Human Cell, 2021)
Renal fibrosis is a pathologic change in chronic kidney disease (CKD). MicroRNAs (miRNAs) have been shown to play an important role in the development of renal fibrosis. However, the biological role of miR-27b-3p in renal fibrosis remains unclear. Thus, this study aimed to investigate the role of miR-27b-3p in the progression of renal fibrosis. In this study, HK-2 cells were stimulated with transforming growth factor (TGF)-β1 for mimicking fibrosis progression in vitro. The unilateral ureteric obstruction (UUO)-induced mice renal fibrosis in vivo was established as well. The results indicated that the overexpression of miR-27b-3p significantly inhibited epithelial-to-mesenchymal transition (EMT) in TGF-β1-stimulated HK-2 cells, as shown by the decreased expressions of α-SMA, collagen III, Fibronectin and Vimentin. In addition, overexpression of miR-27b-3p markedly decreased TGF-β1-induced apoptosis in HK-2 cells, as evidenced by the decreased levels of Fas, active caspase 8 and active caspase 3. Meanwhile, dual-luciferase assay showed that miR-27b-3p downregulated signal transducers and activators of transcription 1 (STAT1) expression through direct binding with the 3′-UTR of STAT1. Furthermore, overexpression of miR-27b-3p attenuated UUO-induced renal fibrosis via downregulation of STAT1, α-SMA and collagen III. In conclusion, miR-27b-3p overexpression could alleviate renal fibrosis via suppressing STAT1 in vivo and in vitro. Therefore, miR-27b-3p might be a promising therapeutic target for the treatment of renal fibrosis.

MiR-501-3p promotes osteosarcoma cell proliferation, migration and invasion by targeting BCL7A - Jinliang Dai; Lin Lu; Lixin Kang; Jian Zhang (Human Cell, 2021)

Upregulation of long noncoding RNA XIST has anticancer effects on ovarian cancer through sponging miR-106a - Ting Guo; Donglan Yuan; Wei Zhang; Dandan Zhu; Aifang Xiao; Guangyao Mao; Wenjuan Jiang; Mei Lin; Jun Wang (Human Cell, 2021)

Amniotic fluid mesenchymal stem cells repair mouse corneal cold injury by promoting mRNA N4-acetylcytidine modification and ETV4/JUN/CCND2 signal axis activation - Xinfeng Fei; Yuying Cai; Feng Lin; Yongyi Huang; Te Liu; Yan Liu (Human Cell, 2021)
Severe corneal injury is one of the main causes of loss of visual function. Mesenchymal stem cells (MSCs) have the ability to repair damaged cells in vivo. The present study aimed to explore whether MSCs could function as a cell therapy tool to replace traditional methods to treat corneal injury. CD44 + /CD105 + mesenchymal stem cells isolated from mouse amniotic fluid (mAF-MSCs) were injected into mice after cryoinjury to induce corneal endothelial cell injury. Histopathological assays indicated that mAF-MSCs could promote the growth of corneal epithelial cells, reduce keratitis, and repair the corneal damage caused by low temperature. cDNA microarray analysis revealed that the mAF-MSCs affected the expression patterns of mRNAs related to cell proliferation and differentiation pathways in the mice after transplantation. The results of quantitative real-time PCR and western blotting revealed that NAT12, NAT10, and the ETV4/JUN/CCND2 signaling axis were elevated significantly in the mAF-MSC-transplantation group, compared with those in the phosphate-buffered saline-treated groups. High performance liquid chromatography–mass spectroscopy results revealed that mAF-MSCs could promote mRNA N4-acetylcytidine (ac4C) modification and high expression of N -acetyltransferase in the eyeballs. RNA immunoprecipitation-PCR results showed that a specific product comprising Vegfa , Klf4 , Ccnd2 , Jun , and Etv4 mRNA specific coding region sites could be amplified using PCR from complexes formed in mAF-MSC-transplanted samples cross-linked with anti-ac4C antibodies. Thus, mouse amniotic fluid MSCs could repair the mouse corneal cold injury by promoting the ETV4/JUN/CCND2 signal axis activation and improving its stability by stimulating N4-acetylcytidine modification of their mRNAs.

Mild acidity likely accelerates the physiological matriptase autoactivation process: a comparative study between spontaneous and acid-induced matriptase zymogen activation - Bailing Jia; Hamishi A. Thompson; Robert B. Barndt; Yi-Lin Chiu; Mon-Juan Lee; See-Chi Lee; Jehng-Kang Wang; Hung-Jen Tang; Chen-Yong Lin; Michael D. Johnson (Human Cell, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

miR-597-5p inhibits cell growth and promotes cell apoptosis by targeting ELK1 in pancreatic cancer - Shizong Li; Xianglu Li; Xuehua Xing; Lin Wang (Human Cell, 2020)

The spatiotemporal control of human matriptase action on its physiological substrates: a case against a direct role for matriptase proteolytic activity in profilaggrin processing and desquamation - Chen-Yong Lin; Jehng-Kang Wang; Michael D. Johnson (Human Cell, 2020)

Spermatogenesis-associated changes of fucosylated glycolipids in murine testis - Masao Iwamori; Shigeki Adachi; Bei Lin; Kyoko Tanaka; Daisuke Aoki; Taisei Nomura (Human Cell, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Circ_ANKIB1 stabilizes the regulation of miR-19b on SOCS3/STAT3 pathway to promote osteosarcoma cell growth and invasion - Yi-xin Du; Lin-xin Guo; Han-song Pan; Yi-min Liang; Xiang Li (Human Cell, 2020)

LncRNA SNHG3 promotes cell proliferation and invasion through the miR-384/hepatoma-derived growth factor axis in breast cancer - Qiuhong Ma; Xiangqin Qi; Xiaona Lin; Liang Li; Libo Chen; Wei Hu (Human Cell, 2020)

SIRT1 promotes GLUT1 expression and bladder cancer progression via regulation of glucose uptake - Jia Chen; Lin Cao; Zhiqiu Li; Yuanwei Li (Human Cell, 2019)

KLP-PI: a new prognostic index for luminal B HER-2-negative breast cancer - Chuanmeng Pan; Adheesh Bhandari; Yehuan Liu; Erjie Xia; Lizhi Lin; Shixu Lv; Ouchen Wang (Human Cell, 2019)

Microvesicles derived from human bone marrow mesenchymal stem cells promote U2OS cell growth under hypoxia: the role of PI3K/AKT and HIF-1α - Shanshan Lin; Bo Zhu; Guozhi Huang; Qing Zeng; Chuhuai Wang (Human Cell, 2019)

Therapeutic activity of plant-derived alkaloid conophylline on metabolic syndrome and neurodegenerative disease models - Kazuo Umezawa; Itaru Kojima; Siro Simizu; Yinzhi Lin; Hitomi Fukatsu; Naoki Koide; Yukiomi Nakade; Masashi Yoneda (Human Cell, 2018)

The determination of sex type of the cultured murine cell with quantitative PCR technique - Qian Wan; Liang Ni; Lintao Wu; Lin Zhang; Mianxue Liu; Xiaohui Jiang (Human Cell, 2015)

Effects of extracellular calcium on viability and osteogenic differentiation of bone marrow stromal cells in vitro - Shaowen Cheng; Wei Wang; Zhongqin Lin; Ping Zhou; Xiaolei Zhang; Wei Zhang; Qingyu Chen; Dongquan Kou; Xiaozhou Ying; Yue Shen; Xiaojie Cheng; Ziming Yu; et al. (Human Cell, 2013)

Regulation of pericellular proteolysis by hepatocyte growth factor activator inhibitor type 1 (HAI-1) in trophoblast cells - Kazuyo Kohama; Makiko Kawaguchi; Tsuyoshi Fukushima; Chen-Yong Lin; Hiroaki Kataoka (Human Cell, 2012)